Pengaruh Gaya Kepemimpinan Dan Dukungan Organisasi Terhadap Komitmen Organisasi Dan Kinerja Pegawai Disparekrafbudpora Kabupaten Gresik - Zulfa Aulia Putri; Endah Susilowati (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
Indonesia is currently experiencing enormous changes, namely being in the era of globalization and free trade, where companies are required to be able to compete with other countries in order to maintain the existence of their companies (Rohayatin, 2021:2). On the other hand, government organizations are also required to have better good governance, this can be seen by the Indonesian people becoming increasingly critical of everything the government does (Dwiyanto, 2021:1). The public demands a good governance pattern through the principles of good governance (transparency, accountability and credibility) (Imbaruddin, 2019: 86). Good governance is basically a concept that refers to the process of achieving decisions and their implementation that can be held accountable together as a consensus reached by the government, citizens and the private sector for the administration of government (Prokomsetda, 2017). This research was conducted with the aim of determining the influence of leadership style and organizational support on organizational commitment and employee performance at the Gresik Regency Tourism and Creative Economy, Culture, Youth and Sports Department.